Efektivitas dan Efisiensi e-Procurement Pengadaan Barang Konstruksi - Chamsudi, Danie Hayam Mada; Setyarto, Aries; Rahardjo, Sri; Sectio, Devin Igel; Bijaksana, Gena; Faturachman, Muhammad Rafli (Jurnal Sistem Transportasi & Logistik, 2021)
Purpose of this study is to analyze the effectiveness and efficiency of PT Metal Bakrie Industries after implementing E-Procurement to its whole procurement activities. To achieve the right and targeted research objectives, the authors formulate a problem regarding whether there are differences in effectiveness and efficiency before and after using E-Procurement at PT Metal Bakrie Industries with effectiveness and efficiency as the independent variable and E-Procurement as the dependent variable. The total population of PT Bakrie Metal Industries staff itself is 38, but only 30 people are taken as samples in this study. The software used by researchers in processing this data is SPSS version 25. This study uses a quantitative approach with data analysis techniques including instrument testing (validity and reliability) and paired t test. Based on the results of this study, after implementing E-Procurement, effectiveness and efficiency were considered better than before implementing E-Procurement. In addition, based on the paired t test, it is said that there is a difference between effectiveness and efficiency before and after using E-Procurement.